Atitudes e percepções dos participantes de um curso de capacitação dirigido a hospitais gerais frente ao álcool, alcoolismo e alcoolista - Vieira, Camila Barcelos (2017)
The loss of abusive use of psychoactive substances such as alcohol makes them one of the main public health problems. However, the literature emphasizes that the professionals who work in the social assistance network have a deficient training to deal with the issue. Thus, permanent education becomes an important training tool for these professionals. Attitudes and beliefs have been used as a benchmark for training in alcohol and other drugs. Thus, the objective of this study is to measure attitudes and understand the conceptions of general hospital professionals regarding alcohol, alcoholism and alcoholism, before and after the training provided by the Regional Reference Center on Drugs of Espírito Santo (CRR-ES). It is an exploratory, descriptive, comparative, quantitative and qualitative approach, using primary and secondary data. The study population comprised 31 professionals (quantitative study) and 6 social workers (qualitative study) that were approved in the course offered by the CRR-ES. The "Attitudes Scale facing Alcohol, Alcoholism and people with disorders related to the use of alcohol”(EAFAA) was used as instrument before and after the course and socio-demographic questionnaire, which gave rise to the database and semi-structured interview script Applied after the course. The quantitative data were analyzed in the Statistical Package for the Social Science (SPSS) version 22, while the qualitative data were studied through analysis of thematic content of Bardin. It was observed that there was a positive change in the attitudes of the professionals, especially regarding the work with the person with disorder related to alcohol use. However, some aspects related to attitudes towards alcohol and alcoholism remain a moralizing concept. Furthermore, the professionals presented poor knowledge regarding prevention of the use and abuse of psychoactive substances, but a good level of knowledge regarding the diagnostic aspects of substance dependence. Finally, the research highlights the importance of ongoing training processes in alcohol and other drugs to improve the quality of care. However, this is not the only way to achieve this goal, and it is necessary to strengthen the network and develop public policies that reject stigmatizing positions.